Traditional cattle breeding practices and rate of inbreeding in the mid rift valley of Oromia, Ethiopia - Aman Gudeto; Tadele Mirkena; Tesfaye Kebede (International Journal of Veterinary Science and Research - Peertechz Publications, 2021)
The study was conducted in Adami Tulu Jidokombolcha, Bora, Dodola, Shala and Negele-Arsi districts with the objective of assessing cattle breeding practices and the rate of inbreeding. Two hundred forty respondents were identified using random sampling techniques. The study's results indicated that farmers traditionally use names and ear cuts to identify their local cattle. Body size was ranked as the primary selection criteria for bulls, while reproductive fitness and milk yield traits were primordial selection criteria for cows. Many of the respondents rear bulls for draught purposes, while few of them rear them for breeding purposes. The study indicated that breeding was mostly panmectic as most of the bulls were owned communally. The findings revealed that the majority of respondents were unaware of the negative effects of inbreeding. Most of the respondents practiced culling of unproductive cattle. Poor reproductive fitness and milk yield were frequently used as primary culling criteria for cows, while poor draft power and old age were ranked as prime culling criteria for male cattle. The information generated on farmers' breeding practices should be used as a baseline for future cattle breeding improvement strategy in the studied and similar areas.